Optical Biopsy of the Upper GI Tract Using Fluorescence Lifetime and Spectra - Nie, Zhaojun; Yeh, Shu-Chi Allison; LePalud, Michelle; Badr, Fares; Tse, Frances; Armstrong, David; Liu, Louis W. C.; Deen, M. Jamal; Fang, Qiyin (Frontiers in Physiology, 2020)
Screening and surveillance for gastrointestinal (GI) cancers by endoscope guided biopsy are invasive, time-consuming, and has the potential for sampling error. Endogenous fluorescence spectra of tissue containing biochemical and physiological information that may enable real-time, objective diagnosis when combined with endoscopic images. We first briefly reviewed optical biopsy modalities for GI cancer diagnosis with a focus on fluorescence-based techniques. In an ex vivo pilot clinical study, we measured fluorescence spectra and lifetime on fresh biopsy specimens obtained during routine upper GI screening procedures. Our results demonstrated the feasibility of rapid acquisition of time-resolved fluorescence spectra from fresh GI mucosal specimens. We also identified spectroscopic signatures that differentiate normal mucosa from the esophagus, stomach, and duodenum.